Priorities for reforming the WTO / Priorități de reformare a OMC - LOBANOV Natalia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The article examines how the WTO (World Trade Organization) is implementing reforms to maintain its role as a forum for multilateral negotiations and global trade arbiter. Economic crises cause increased protectionism, but the WTO itself has been in crisis for some time and cannot fully withstand the return of trade barriers. It is especially important at a time when global solutions are essential to set priorities that make economic globalization more open, inclusive, balanced and beneficial for all by updating rules and strengthening safeguards. We note that the WTO is to be reformed to address current issues such as its negotiating function, dispute settlement system and transparency in its work.